2016
DOI: 10.1016/j.psyneuen.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Daily family stress and HPA axis functioning during adolescence: The moderating role of sleep

Abstract: The present study examined the moderating role of sleep in the association between family demands and conflict and hypothalamic-pituitary-adrenal (HPA) axis functioning in a sample of ethnically diverse adolescents (n = 316). Adolescents completed daily diary reports of family demands and conflict for 15 days, and wore actigraph watches during the first 8 nights to assess sleep. Participants also provided five saliva samples for 3 consecutive days to assess diurnal cortisol rhythms. Regression analyses indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 124 publications
3
39
2
1
Order By: Relevance
“…Our day-to-day findings, along with those from Chiang et al (2016) regarding average levels of daily assistance behavior, indicate that morning levels of cortisol, including waking levels and the cortisol awakening response, may be important biomarkers of chronic family stressors or need for family assistance for adolescents, in particular.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our day-to-day findings, along with those from Chiang et al (2016) regarding average levels of daily assistance behavior, indicate that morning levels of cortisol, including waking levels and the cortisol awakening response, may be important biomarkers of chronic family stressors or need for family assistance for adolescents, in particular.…”
Section: Discussionmentioning
confidence: 56%
“…For example, among adolescent girls, attenuated cortisol responses to stress have been associated with accelerated pubertal development (Saxbe, Negriff, Susman, & Trickett, 2015), and a blunted cortisol awakening response and total diurnal output interacted with stressful events to predict future depressive symptoms (Schuler et al, 2017). While associations between family assistance behaviors and psychosocial and immune outcomes have been explored in studies of Latino youth and families (e.g., Chiang et al, 2016; Fuligni et al, 2009; Telzer et al, 2015), our study is the first to identify the temporal ordering of such processes from day to day, as opposed to weekly averages, with intensive assessments of stress-sensitive physiological markers.…”
Section: Discussionmentioning
confidence: 99%
“…These items were selected because they have previously been shown to be stressful for adolescents (Chung, Flook, & Fuligni, 2009; Fuligni et al, 2009; Nishina & Juvonen, 2005). Consistent with previous research on daily stress (Chiang et al, 2016; Grzywacz, Almeida, & McDonald, 2002; Sin, Graham-Engeland, Ong, & Almeida, 2015), affirmative responses were summed and recoded as 0 or 1 for each day to indicate whether any one of the stressors occurred that day. The average of recoded scores across days was subsequently computed to indicate the proportion of days that at least one stressor occurred.…”
Section: Methodsmentioning
confidence: 99%
“…We examined several types of stressors, including major life events in the past year, daily negative social interactions across a 15-day period, and the early psychosocial family climate. Given that prior work has tied each of these stressors to health outcomes and biological functioning in both youth and adults (Carroll et al, 2013; Chiang et al, 2016; Fuligni et al, 2009; Kershaw et al, 2014; Loucks, Almeida, Taylor, & Matthews, 2011; Miller & Chen, 2010; Pyykkönen et al, 2010; Stroud, Chen, Doane, & Granger, 2016), we did not hypothesize any differential effects according to stressor type. Instead, we hypothesized that all three types of stress would be associated with sub-optimal biological profiles, as evidenced by dampened cortisol and heightened IL-6 responses to acute stress.…”
mentioning
confidence: 99%
“…Youth and their parents completed a series of questionnaires, provided measures for several biomarkers, and completed a daily diary protocol at each wave. More details on the parent study can be found elsewhere (Chiang et al, 2015a, 2016). …”
Section: Methodsmentioning
confidence: 99%